Employment, flexible working and the family - Crompton, Rosemary (The British Journal of Sociology, 2002)
This paper assesses some of the implications of one of the major social changes to have taken place in the West during the second half of the twentieth century — that is, the increased employment of women, together with normative changes in gender relations and in women's expectations. These changes have been linked to an increase in individualism, which itself is associated with the transcendence of ‘first modernity’. Thus it is suggested that new approaches to social analysis are required (Beck). Here it is argued that, rather than develop completely new approaches in order to grasp the changes that are under way, the ‘economic’ and the ‘social’ (that is, employment and the family) should be seen as intertwined, rather than approached as separate phenomena. Past debates in feminism, changes in the family, and flexible employment are critically examined. The growing tensions between employment and family life are discussed. It is argued that these changes are associated with the intensification of capitalist development, rather than reflecting a fundamental transformation of society. Existing approaches to the analysis of social change, including Polanyi's analysis of the development of ‘counter-movements’ against the ‘self-regulating’ market, will, therefore, still be relevant to our enquiries. In the concluding section, a programme of research that would examine these changes is outlined.
Sociology
Keywords: capitalism; family; flexible employment; gender; modernity

Theorizing the 'Third Sphere': A Critique of the Persistence of the 'Economistic Fallacy.' - Adaman, Fikret; Madra, Yahya M. (Journal of Economic Issues, 2002)
The paper seeks to investigate, from a methodological and ontological perspective, different ways of theorizing the third sphere–the set of activities that can be captured by neither the price mechanism of the markets nor by governmental transactions. The first aim is to elucidate the constitutive elements of the third sphere by deploying Polanyi's forms of integration (reciprocity, redistribution, and exchange). The second is to survey the ontologically individualist and methodologically formalist literature on the third sphere. After elucidating the coexisting sets of behavioral essences in contemporary ontologically individualist and methodologically formalist models of third-sphere activities, the paper claims that this proliferation of behavioral essences can only lead to a methodological impasse. The paper concludes that only with a committed recognition of the heterogeneity of the economy and the endogeneity of the economic subject will it become possible to better grasp the richness of third sphere activities.
Economics
Keywords: current heterodox approaches: institutional; economic methodology; economistic fallacy

Chapter 7: Karl Polanyi - Rogerson, Kenneth S.; May, Christopher (Key Thinkers for the Information Society, 2002)
This article presents Karl Polanyi's analysis of the dynamic relationships between economy and society in the information age. Of the many concepts Karl Polanyi provides in his analysis of economic relations, three stand as carefully calculated assumptions about the relationship between society and economy: the embeddedness of information in society, the commoditization of information and the existence of a double movement in the information revolution. Information has always been embedded in societal interactions. To emphasize this point, he said that the simple flow of information seems to have little effect in and of itself on the outcome of social interchanges. In Polanyi's words, it is also embedded in other social relations, such as political, economic, cultural, or health-related discussions and actions. On the issue of information commoditization, Polanyi takes a different view. His logic indicates that there will be negative social consequences associated with it. One example is digital divide or the discrepancies on a global or national level between those who have access to information through new technologies and those who do not. With regards to the existence of double movement, Polanyi believed that there are two opposing forces-economic liberalism and social protection-present during the industrial revolution. However, this is not easy to see in the information age because of simple paradox. First, people who would eschew the uses of technology for ideological reasons,may turn to it for other reasons. And second, there is only a protest of a specific issue and not the imbalance of information flows or the ownership of information dissemination methods.
Information Science; Philosophy; Communications
Keywords: commercialization; communication revolution; digital divide; industrial revolution; information technology; liberalism

Politics, the state and the impulse for social protection : the implications of Karl Polanyi's ideas for understanding development and crisis - Putzel, James (London School of Economics Crisis States Research Centre working papers series 1, 18., 2002)
This short paper discusses how some of Karl Polanyi's key ideas can help shed light on the processes of development and crisis in the world today. It begins by taking up the role of economic liberalisation and the state. Then it discusses Polanyi's identification of the 'impulse' for 'social protection' and suggests it is crucial to an understanding not only of the role of the state in development but also politics in the developing world. It finishes by applying some of these ideas to understanding the actions of 11th September, and the crisis related to terrorism in the developing world today.
Development Studies
Keywords: development; economic theory; political institutions; social history; social problems; social protection; social reform

Great Transformations: Economic Ideas and Institutional Change in the Twentieth Century - Blyth, Mark (Cambridge University Press, 2002)
Mark Blyth argues that economic ideas are powerful political tools as used by domestic groups in order to effect change since whoever defines what the economy is, what is wrong with it, and what would improve it, has a profound political resource in their possession. Blyth analyzes the 1930s and 1970s, two periods of deep-seated institutional change that characterized the twentieth century. Viewing both periods of change as part of the same dynamic, Blyth argues that the 1930s labor reacted against the exigencies of the market and demanded state action to mitigate the market's effects by "embedding liberalism" and the 1970s, those who benefited least from such "embedding" institutions, namely business, reacted against these constraints and sought to overturn that institutional order. In Great Transformations, Blyth demonstrates the critical role economic ideas played in making institutional change possible and he rethinks the relationship between uncertainty, ideas, and interests on how, and under what conditions, institutional change takes place. Mark Blyth is an assistant professor of political science at the Johns Hopkins University specializing in comparative political economy. He has taught at Columbia University, and at the University of Birmingham, UK. Blyth is a member of the editorial board of the Review of International Political Economy.
Political Science
Keywords: economic policy; political economy; political science; public policy

Anomie, Social Change and Crime - Bernburg, Jon Gunnar (British Journal of Criminology, 2002)
The last decade has seen a revived interest in using anomie theory in crime and deviance research. The present paper contributes to this development by offering an examination of a particular extension of anomie theory, namely, Messner and Rosenfeld's Institutional-Anomie theory. Explicating Institutional-Anomie theory relative to the sociologies of Durkheim, Merton and Polanyi, I find that this theory goes beyond Merton by using a strain of thought that is critical of liberal society. By bringing in the notion of the disembedded market economy, a central notion in the institutionalism of Polanyi and Durkheim, this theory links crime, anomie, and contemporary social change. I also discuss some of the limitations of linking crime with societal level processes in a Durkheimian rather than Mertonian manner.
Sociology; Criminology
Keywords: DURKHEIM; Emile; MERTON; Robert; anomie; crime; criminology; disembeddedness

Place, Capitalism, and Democratic Efficacy - Kogl, Alexandra (2002)
Political Science
Keywords: DELEUZE; Gilles; capitalism; democracy; democratic; economy; efficacy; empire; place; political; theory

The Great Transformation at Sea: Fictitious Commodities and the Crisis of Marine Fisheries - Ziegelmayer, Eric (2002)
Challenging contemporary debates concerning the regulation of ocean fisheries, this paper deploys theoretical insights developed by Karl Polanyi. In The Great Transformation, Polanyi documented the consequences of the establishment of market economy upon European society, and thereby upon the entire planet. The concept of the self-regulating market, according to Polanyi was based on three "commodity fictions" of land, labor and money; the extension of this concept to all of the economic institutions of society he called "market utopianism." This paper extends Polanyi’s fictitious commodity thesis to the living resources of the ocean and argues that the roots of the contemporary problems of the world’s fisheries originate in the exposure of nature to a market economy. Concerned with the future governance of ocean resources and democracy in fishery regulation, the paper examines the globalization of the fishing industry in comparative and historical perspective to illuminate the validity of Polanyi’s theory. While there can be no final agreement as to the constitution of "good society", a useful starting point for debate is provided by the work of Karl Polanyi. A good society, he claims, is a society capable of producing goods, and a necessary condition of life in such a society is that human beings and nature are not treated as commodities
Political Science
Keywords: capitalism; democracy; economy; fictitious commodities; fisheries; fishery policy; political; property; rights; saltwater fishing

Market Liberalism and Social Protection: Hayek, Durkheim and Polanyi in Theoretical Perspective - Akturk, Sener (Journal of Academic Studies, 2002)
Examines the views of neoclassicist Friedrich A. Hayek, sociologist Emile Durkheim and Karl Polanyi on liberalism. Relationship between the individual, the market economy and society; Features of Hayekian neoclassical economics; Information on Polanyi's book 'The Great Transformation.'
Political Science
Keywords: DURKHEIM; Emile; Great Transformation; The (Book); HAYEK; Friedrich A. von (Friedrich August); 1899-1992; liberalism; social protection

The Contested Sovereignty of the Firm - Dietrich, Michael (Review of Political Economy, 2002)
This paper suggests that the firm can be analysed as a regulated system of contested sovereignty. The economic literature on the firm is categorised in terms of four different perspectives on sovereignty identified using the twin factors of power and authority. But rather than any single perspective being identified as analytically superior, it is argued that a system of contested sovereignty should be based on all four perspectives. Following this, a Polanyi-inspired analysis of firm regulation is presented in which the regulation of the firm emerges to control the costs of free markets. However, this regulation depicts firm sovereignty as complex and contested rather than simply an optimal response to market failures.
Economics
Keywords: business enterprises; economics and literature; firm regulation; firm sovereignty; political economy

The 'new contractualism', social protection and the Yeatman thesis - Gaby Ramia (Journal of Sociology, 2002)
An important characteristic of public policy formulation over the 1980s and 1990s, particularly in the English-speaking countries, has been the increasing use of contractual principles as regulatory tools. The 'new contractualism' represents the recent re-emergence and adaptation of the social contract of the 17th and 18th centuries and the classical legal contract that emerged in the 19th century. The work of Anna Yeatman provides the most cogent and influential, non-neo-liberal scholarly appraisal of the new contractualism. Yeatman argues that the current contractualist agenda is consistent with equality of opportunity, occasioning a redefinition of citizenship so as to improve on the discourse of social protection. This paper argues that any attempt to remove social protection flawed though it is from discussions of the new contractualism is artificial. The social justice implications of such a position are perilous, for policy formulation has not yet entered a phase in which social protection can be superseded in a way which does not violate the rights of the socio-economically disadvantaged.
Sociology
Keywords: English-speaking countries; YEATMAN; Anna; citizenship; commodity fiction; contractualism; double movement; equality; fictitious commodities; governance; human rights; political planning; social justice; social movements; social protection; sociology

Ecosocialisation and environmental planning: a Polanyian approach - Low, Nicholas (Environment & Planning A, 2002)
Discusses a Polanyian approach to environmental planning, foregrounding the concept of ecosocialization. Global problems of urban modernity; Ecological modernization and the transformation of capitalism; Discussion on ecological Marxism and the transition to socialism; Polanyian perspective for environmental planning.
Geography
Keywords: capitalism; environmental engineering; human ecology

Towards a Theory of Values-Based Labeling - Barham, Elizabeth (Agriculture and Human Values, 2002)
An outline of a theory of values-based labeling as a social movement argues that it is motivated by the need to re-embed the agro-food economy in the larger social economy. A review of some basic premises of embeddedness theories derived from the work of Karl Polanyi reveals their connection to particular values-based labeling efforts. From this perspective, values-based labeling presents itself as primarily an ethical and moral effort to counter unsustainable trends within presently existing capitalism. These labels distinguish themselves from ordinary commercial labels by a focus on process and on quality. Evaluating the transformative potential and progressive nature of values-based labeling poses a key challenge. One avenue for gauging this potential is conventions theory. This approach can be adapted to consider the decision making processes that go on within values-based labeling groups, as well as consumer decision making based on such labels, as instances of what is termed a politics of ethical judgment. The conclusion emphasizes the need for more research in this area and suggests how it could be furthered.
Sociology
Keywords: agricultural policy; agro-food economy; embeddedness; food policy; household production and intrahousehold allocation; marketing; relation of economics to social values; social economy

Transnational Pharmaceutical Corporations and Neo-Liberal Business Ethics in India - D'Mello, Bernard (Journal of Business Ethics, 2002)
The author critiques the expedient application of market valuation principles by the transnational corporations and other large firms in the Indian pharmaceutical industry on a number of issues like patents, pricing, irrational drugs, clinical trials, etc. He contends that ethics in business is chiseled and etched within the confines of particular social structures of accumulation. An ascendant neo-liberal social structure of accumulation has basically shaped these firms' sharp opposition to the Indian Patents Act, 1970, government administered pricing, etc. The author contends that the practice of neo-liberal economics is strongly associated with a "one dimensional" ethics that privileges market valuation principles over all others. This seems to inevitably generate a social counter-movement that struggles for social protections. He critiques neo-liberal business practices from a perspective that derives from the work of the economic anthropologist Karl Polanyi. Before the present phase of liberalization in India, markets were "managed", but without a "welfare state" in place. Moving toward deregulation of the markets without a welfare state in place is unethical. Keeping the debilities of the institutional framework of public policy in mind, the author adopts a Polanyian perspective that places its trust and hope in the growing social legitimacy of the counter-movement in opposition to both neo-liberal business practices and the degenerate behavior of state agencies.
Political Science; Economics
Keywords: India; business ethics; intellectual property; international business enterprises; pharmaceutical industry; socialism

The World Bank or Polanyi: Markets, Poverty and Social Well-being in Latin America - Kirby, Peadar (New Political Economy, 2002)
Explores the role of markets in achieving social well-being in Latin America, highlighting alternatives theories for this relationship based on the work of Karl Polanyi. Role of markets in reducing poverty; Relation between markets and social institutions; Ways in which market liberalization is damaging the livelihoods of the poor.
Political Science
Keywords: Latin America; markets; poverty; social institutions

Globalization and Democracy: A New 'Great Transformation'? - Munck, Ronaldo (Annals of the American Academy of Political & Social Science, 2002)
Examines the relationship between democracy and development to set the scene for the pressing contemporary issue of how globalization might affect democracy and vice versa. Reference to the work of Karl Polanyi who posited a dual movement of market expansion matched by increasing social control over it; Impact of globalization.
Sociology; Political Science
Keywords: POLANYI; Karl; 1886-1964; democracy; double movement; economic development; globalization

The Construction of Market Institutions in Russia: A View from the Institutionalism of Polanyi - Sánchez-Andrés, Antonio; March-Poquet, José M. (Journal of Economic Issues, 2002)
This article presents information on the construction of market institutions in Russia and includes the institutional conception provided by analyst Karl Polanyi. Polanyi's main ideas will be expounded in regard to his interest in analyzing the transition. These ideas will be adapted to the object of study and then specified so that they will be efficient criteria for analyzing the present economic transition. Second, the results obtained will be applied to the Russian case, and an attempt will be made to draw some conclusions about whether Russia is moving toward a market economy. Although several distinct parts of the work of Polanyi may be of great interest in analyzing the transition process that is occurring in countries that until the 1990s were organized by central planning.. This paper discusses only the aspects which are most closely related to the construction of market economies will be mentioned. According to Polanyi, the commercialization of productive factors and money are among the determining elements for the construction of an economic market.
Economics
Keywords: Russia (federation); analysts; central planning; economic reform; industrialization; markets; transition economies

The Great Depression and the Decline of Liberal Capitalism: Polanyi and Schumpeter - Trigilia, Carlo (Economic Sociology, 2002)
This chapter contains section titled: * Market Domination and Society's Self-Defense * The Decline of the Bourgeoisie and Anti-Capitalist Policies * Analytical Convergence and Political Divergence
Sociology
Keywords: SCHUMPETER; Joseph Alois; 1883-1950; capitalism; depression; economic level; economic sociology; international relations; social conditions